Virtualization Sparks Security Concerns. - Vaughan-Nichols, Steven J. (Computer (00189162), 2008)
The article discusses virtualization, which in 2008 is soon to become the standard technology for businesses. The author defines virtualization as a single computer or server which simultaneously runs multiple operating systems or multiple sessions of one operating system. Topics include users optimizing hardware utilization and the maximization of jobs performed by a single central processing unit (CPU). Also discussed are virtualized systems which cannot be secured the same way as physical systems and the different requirement levels for security systems.